ENDOMARKETING AND JOB SATISFACTION IN CREDIT UNIONS - de Mello, Fernanda; Marschner, Paulo Fernando; Franca Zonatto, Patrines Aparecida (Revista Gestão Organizacional, 2025)
Purpose: This study aimed to analyze the relationship between endomarketing and job satisfaction in credit unions. Method/Approach: The research employed a quantitative and descriptive approach, collecting data through a survey. Data analysis involved descriptive statistics, reliability assessment, and Pearson correlation coefficient calculation. Main findings: The results revealed a positive correlation between implemented internal marketing strategies and the level of employee satisfaction in credit unions. Endomarketing demonstrated its ability to establish a direct relationship with job satisfaction through the implementation of marketing practices targeted at the internal audience. Theoretical/Practical/Social Contributions: Endomarketing strategies and initiatives aim to promote the well-being of employees within the organizational environment, leading to a significant improvement in job satisfaction. Investing in endomarketing strategies is considered essential for fostering a healthy work environment in credit unions. Originality/Relevance: This study emphasizes the importance of endomarketing as an effective means to enhance job satisfaction in credit unions, contributing to the understanding and practical application of this relationship.